Transition-Metal-Free Heterocyclization of 1,3-Diynes with Nitriles in the Presence of Aqueous Potassium Hydroxide: Synthesis of 2,4-Disubstituted 5-[(E)-2-Phenylethenyl]-1,3-oxazoles - Ming, Ling; Tang, Jialiang; Zhao, Xiaoming (Synthesis, 2014)
A transition-metal-free heterocyclization of 1,3-diynes and nitriles in the presence of either aqueous potassium hydroxide or cesium hydroxide in 1,4-dioxane at 100 °C was realized. This method provided stereoselectively 2,4-disubstituted 5-[(E)-2-phenylethenyl]-1,3-oxazoles in moderate to good yields.
Keywords: 1,3-diyne; nitrile; heterocyclization; cesium hydroxide; potassium hydroxide